2012
DOI: 10.1111/j.1095-8649.2012.03309.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet overlap among flatfish species in the southern North Sea

Abstract: The diets of two non-commercial flatfish species (solenette Buglossidium luteum and scaldfish Arnoglossus laterna) and two commercial flatfish species (dab Limanda limanda and plaice Pleuronectes platessa) were compared in a study area in the German Bight (southern North Sea) to investigate prey-resource partitioning between these species. The diets of A. laterna and B. luteum mainly comprised crustaceans (harpacticoids, amphipods, cumaceans and decapods), whereas the diet of L. limanda and P. platessa consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 51 publications
3
19
0
3
Order By: Relevance
“…Confirming this, preferential feeding on macrofauna was also found in previous diet studies for both fish species (e.g. Gibson and Ezzi 1980;Bayan et al 2008;Schückel et al 2011) and furthermore, was already found in relatively small fish (L T 's \ 10 cm; Schückel et al 2012). …”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Confirming this, preferential feeding on macrofauna was also found in previous diet studies for both fish species (e.g. Gibson and Ezzi 1980;Bayan et al 2008;Schückel et al 2011) and furthermore, was already found in relatively small fish (L T 's \ 10 cm; Schückel et al 2012). …”
Section: Discussionsupporting
confidence: 68%
“…For details on fish predation on macrofaunal prey groups, see Schückel et al (2011) and Schückel et al (2012). Among different meiofaunal prey groups, harpacticoids were always of primary importance in the diet of each of the studied fish species during all seasons, whereas nematodes dominated the meiofauna community in the study area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, however, ongoing climate change has impacted all compartments of the marine ecosystem, leading to regime shifts of phytoplankton and zooplankton communities (Beaugrand and Ibanez, 2004;Richardson and Schoeman, 2004;McQuatters-Gollop et al, 2007), distributional shifts of benthos Birchenough et al, 2015), and deepening of fish assemblages (Dulvy et al, 2008). Cod has disappeared almost completely from the southern North Sea due to overfishing and climate change (Daan et al, 2005;Beaugrand and Kirby, 2010), and the region has changed into flatfish dominated communities, including abundant commercial species (e.g., Pleuronectes platessa) and particularly high abundances of small, non-commercial, mesopredatory species (e.g., Buglossidium luteum) (Ehrich et al, 2007;van Hal et al, 2010;Schückel et al, 2012). Furthermore, mackerel is extending its range northwards into the sub-Arctic (Stenevik and Sundby, 2007;Utne et al, 2012).…”
Section: Introductionmentioning
confidence: 99%